METODE PROJECT BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP ANALISIS INSTRUMEN PADA MATA KULIAH EVALUASI PEMBELAJARAN MATEMATIKA - Nusantari, Diah Oga; Ahmad , Deni Nasir; Zulkarnain, Ihwan (TRANSFORMASI, 2024)
Student-centered learning is very essential in producing graduates who have good competencies and are ready to work. As prospective teacher, Matematics Education students are expected to have competence in evaluating the implementation of learning in the classroom. This research aims to determine the increase in the ability to understand the concept of instrument analysis in the Mathematics Learning Evaluation course after using the Project Based Learning (PjBL) method. The research was conducted using the classroom action research method. The result show that in the cognitive domain, students can determine the correct formula according to the type of item on the instrument. In the intrapersonal domain, the search for real knowledge and various problems as well as the application of knowledge that is not limited only to theory can increase the development of students’ affection. As for teh interpersonal domain, students are taught to educate themselves to do self regulationt and to be cohesive among them to create a solid team work. Working on team also will improce student leadership. The increase in the ability to understand the concept of instrument analysis shows that the PjBL method can be used in other concepts in the Mathematics Learning Evaluation course, or in other courses.